2020
DOI: 10.3390/nu12041052
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Diversity and All-Cause and Cause-Specific Mortality in Japanese Community-Dwelling Older Adults

Abstract: We examined associations between dietary diversity and all-cause and cause-specific mortality in 386 men and 413 women (age range, 60–79 years at baseline) who took part in the National Institute for Longevity Sciences-Longitudinal Study of Aging study from 1997 to 2000. Dietary intake was assessed using three-day dietary records and photographs. The Quantitative Index for Dietary Diversity was used to determine the dietary diversity among thirteen food groups. Dietary diversity score and each food intake were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 32 publications
5
33
0
Order By: Relevance
“…We performed a meta-analysis by combining the continuous NHANES prospective study results with the findings of previous prospective cohort studies of mushroom intake and all-cause mortality. Our systematic literature search from January 1, 1966, up to May 1, 2021, identified 313 publications, including 170 articles from PubMed, 135 from Web of Science, and 8 from Cochrane Library databases, which two studies reported the association of mushroom consumption with mortality [ 34 , 36 ]. In addition, we manually searched the bibliographies of one retrieved review [ 60 ] and found two more studies [ 35 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We performed a meta-analysis by combining the continuous NHANES prospective study results with the findings of previous prospective cohort studies of mushroom intake and all-cause mortality. Our systematic literature search from January 1, 1966, up to May 1, 2021, identified 313 publications, including 170 articles from PubMed, 135 from Web of Science, and 8 from Cochrane Library databases, which two studies reported the association of mushroom consumption with mortality [ 34 , 36 ]. In addition, we manually searched the bibliographies of one retrieved review [ 60 ] and found two more studies [ 35 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“… Ba et al (2021) [ 34 ] M/F Total: 15,546 M:7047; F:8499 24-h recall Death certificate US Cohort study (NHANES III) 44.3 5826 All-cause Yes vs. No HR: 0.84 (0.73, 0.98) 27 Age, sex, ethnicity-race, US regions, place of residence, education attainment, marital status, BMI, physical activity, total energy intake, fat, carbohydrates, fiber, alcohol, smoke 100+ cigarettes in life, Healthy Eating Index-2005 score. Otsuka et al (2020) [ 36 ] M/F Total: 799 M: 386; F: 413 3-day dietary record National vital statistics records Japan Cohort study 68.1 289 All-cause T3 (27.6 g/d) vs T1 (0 g/d) HR: 0.97 (0.72, 1.32) 15.7 Age, sex, body mass index, education, smoking status, alcohol intake, physical activity, and history of hypertension, dyslipidemia, and diabetes mellitus Leenders M et al (2013) [ 35 ] M/F Total:451,151; M:129,882; F: 321,269 FFQ, dietary history, food record Record linkage with cancer registries, boards of health, and death indices, health insurance records, cancer and pathology registries, next of kin European countries: Denmark, France, Germany, Greece, Italy, the Netherlands, Norway, Spain, Sweden, and UK Cohort study 51.2 25,682 All-cause T3 vs. T1 HR: 0.94 (0.90, 0.98) 13 Age, smoking status, smoking duration, time since stopped smoking, number of cigarettes per day, alcohol, BMI, physical activity, education, processed meat, mutual adjustment between fruit and vegetables Iso H et al (2007) [ 37 ] M/F T: 104,019; M:43,850; F:60,169 Validated FFQ Death rate among participants according to the responses to the diet questionnaire Japan Cohort study Age 40-79 y 16,135 All-cause Men ≥3 vs < 1/wk. Women ≥3 vs < 1/wk RR: 0.97 (0.91, 1.03) RR: 0.96 (0.89, 1.03) 12.7 Age, area of study …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies showed that a higher dietary diversity score (DDS) is inversely associated with some age-related diseases, such as diabetes [17], cognitive decline [18]. Additionally, it has been shown that adherence to a diverse diet reduced the risk of death [19,20]. However, prospective evidence on DDS and ADL disability is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work showed that higher diet diversity was associated with better memory status in adults [ 21 ]. Moreover, prospective studies have suggested that dietary diversity is inversely associated with all-cause mortality in Chinese and Japanese populations [ 22 , 23 ]. However, evidence of dietary diversity in relation to the overall healthy aging process is scarce in the literature.…”
Section: Introductionmentioning
confidence: 99%